Pelaksanaan Program Kerja KKN-Sains Tematik Desa Berbasis Sosialisasi Peran Keluarga Sebagai Salah Satu Pencegahan Bahaya Narkoba Di Desa Mojodowo - Dedy Muharman; Lina Wulandari; M. Izzul Islami; Shofia Kartika Candra; Syahrul Arya Pratama; Ratih Ajeng Azzahro; Sindi Agustin; Virgita Dwi Pridana Putri; Wahyu Amalia Putri; Dwi Karina Fitroh; Herdani Indra Permadi; Rizky Fandiosyah Eka Dinanta; Mar’atul Arifah; Sadidatul Ilmi; Abdera Rouchul Haq; Adek Engga Novendri Angga; Agil Ahdi Susanto; Agung Wijaya; Ahmad Azis Susanto; Rindia Putri Wulandari; Mokhammad Fakhrul Hidayat; Adriyan Awal Maqruf; Wahyu Aditiya; Alvina Novianti; Amrina Rosyada (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Implementation of KKN-Science is one of the community services aimed at solving a problem in the region. In the implementation of this KKN-Science the main focus is to know the role of families towards the dangers of narcotic abuse and the prevention of narcotic dangers in Mojodowo Village. The KKN-Science activities of Mayjen Sungkono Mojokerto University conducted by students and DPL were held on 09-16 December 2023 at Mojodowo Village office, Kembagi, Mojokerto. The benefits of this service activity are aimed at adding insight and education to the public in the prevention of the dangers of narcotics and the relationship of criminal offenses to narcotic abuse. This study uses destriptive research methods with quantitative approach as well as data collection sourced from primary data using socialization and documentation. The study was conducted on parents with teenage children in the vicinity of Mojodowo Village. The results of the study and discussion show that the role of the family is very important in providing broad information, knowledge and understanding of the dangers of drugs and their negative impact on all aspects of life. Obstacles in the prevention of drug harm in the family are differences in the personality of the child, the child's lack of openness to parents, and exposure to a negative social environment. The study's recommendation is that each family supervise and guide adolescents to avoid falling into narcotics.